Widyo Iswara, Prasetyo ANALISIS RASIO PROFITABILITAS UNTUK MENGUKUR KINERJA KEUANGAN: STUDI KASUS PADA PT BATAM JAYA PROPERTINDO (JBT (JURNAL BISNIS dan TEKNOLOGI), 2015)
Financial performance analysis based on profitability ratio of Batam Jaya Propertindo company during the period of 2009-2011. Type of ratio this research is gross profit margin, net profit margin, return on assets, and return on equity. The objective of the research presented here is to know financial performance Batam Jaya Propertindo company during the period of 2009-2011. The result of study presented here to minimize of loss company in next future with used ratio, should be taking decision for anticipated to loss.